PMMA/High-k Self-assembled TiO2/PMMA Multi-layer Gate Dielectric for P3HT Organic Field Effect Transistors - Nongluck Houngkamhang; Kroekchai Inpor; Chanchana Thanachayanont; Seeroong Prichanont; Navaphun Kayunkid (Current Applied Science and Technology, 2021)
In this work, a multi-layer structure of poly (methyl methacrylate)/ titanium dioxide/poly (methyl methacrylate) (PMMA/TiO₂ /PMMA; PTP) was proposed as a top-gate insulator for P3HT-based organic field-effect transistors (OFETs). Adding a TiO₂ interlayer as a high dielectric constant (high-k) material into PMMA film enables the modification of the dielectric constant of the multi-layers PTP film. The content of TiO₂ in the PTP film, which can be varied by changing the number of soaking cycles in TiO₂ solution, plays a crucial rule in modifying the dielectric constant of the PTP film. The higher the TiO₂ content used in the PTP film, the higher the dielectric constant of PTP film can be obtained. However, using high TiO₂ content led to a reduction in the dielectric constant of the PTP film due to leakage current induced by the agglomeration of TiO₂. The utilization of the top-gate insulator containing TiO₂ significantly enhanced several P3HT-OFETs characteristics, e.g., an increase in the Ion/Ioff ratio, and a decrease in the threshold voltage. However, the use of the PTP top-gate insulator with a high content of TiO₂ resulted in regressions in the OFETs characteristics, such as a decrease in carrier mobility and reduction in the Ion/Ioff ratio. OFETs operating at the optimum conditions of the PTP gate-insulator, with PTP thickness of 225 nm and RMS roughness of 20.0 nm, provided a dielectric constant of 7.13, a threshold voltage of -8.49 V, a saturation mobility of 2.2× 10-4 cm²V-1s-1, Ion/Ioff ratio of 37.9, and a subthreshold slope of 0.39 V/decade.
Keywords: Semiconductor materials and devices; Diamond and Carbon-based Materials Research; Advancements in Semiconductor Devices and Circuit Design